The secret of the sea creature - Sutton, Laurie; Neely, Scott (North Mankato, MN Stone Arch Books, 2014)
A day at the beach turns into an adventure when Scooby Doo and the gang encounter a sea monster--and the reader's choices govern what happens next
"A Capstone imprint."
English stories
1 2 13 15
NEW_ZTN_GN
Keywords: Scooby-Doo -- (Fictitious character) -- Juvenile fiction; Detective and mystery stories; Great Dane -- Juvenile fiction; Plot-your-own stories; Sea monsters -- Juvenile fiction; Dogs -- Fiction; Mystery and detective stories; Plot-your-own stories; Sea monsters -- Fiction; Mystery fiction